2000
DOI: 10.1038/sj.ijo.0801404
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin concentrations and obesity in relation to insulin resistance syndrome components among school children in Taiwan—The Taipei Children Heart Study

Abstract: OBJECTIVE: Leptin, an adipose tissue-derived product of the obesity (OB) gene, is an important regulator of energy metabolism and may be associated with the occurrence of insulin resistance and diabetes in humans. The purpose of this study was to evaluate the association of plasma leptin concentration with obesity and the components of insulin resistance syndrome (IRS) among school children in Taiwan. METHODS: After multistage sampling of 85 junior high schools in Taipei, we randomly selected 1264 children (61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 47 publications
3
45
0
3
Order By: Relevance
“…26,27,45,46 Since leptin may modulate IR in ways beyond the effects of adiposity and fat distribution, 47 plasma leptin in combination with BMI has been recognized as a compelling predictor of IR syndrome among school children. 48 In addition, higher leptin concentrations have been found to be associated with impaired arterial distensibility, suggesting that high levels of leptin may have an adverse impact on body fat metabolism, leading to CVD. 49 Therefore, the level of circulating plasma leptin in adolescents may be a powerful predictor for metabolic syndrome disorders and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…26,27,45,46 Since leptin may modulate IR in ways beyond the effects of adiposity and fat distribution, 47 plasma leptin in combination with BMI has been recognized as a compelling predictor of IR syndrome among school children. 48 In addition, higher leptin concentrations have been found to be associated with impaired arterial distensibility, suggesting that high levels of leptin may have an adverse impact on body fat metabolism, leading to CVD. 49 Therefore, the level of circulating plasma leptin in adolescents may be a powerful predictor for metabolic syndrome disorders and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Data based mainly on animal studies also suggest that increased levels of resistin, another molecule produced by adipose tissue, could impair insulin sensitivity (17). There are also data showing a close relationship between leptin levels and insulin resistance in children (24). Recently, it has also been shown that serum levels of retinol-binding protein 4 (RBP4) correlate with insulin resistance in subjects with obesity as well as in those with impaired glucose tolerance (IGT) or T2DM, therefore suggesting that it could be useful in assessing insulin resistance and the associated risk for complications (25).…”
Section: The Role Of Fatty Acids and Adipocytokinesmentioning
confidence: 98%
“…[15][16][17][18][19][20][21][22][23] This sex difference in insulin resistance has usually been attributed to differences in adiposity or pubertal stage, but in studies which have adjusted for these factors 15,18 a residual difference remains which has not been explained. We have shown that girls are substantially (B33%) more insulin resistant than boys at 5 years 24 and in the years leading up to puberty.…”
Section: Introductionmentioning
confidence: 99%